CROSS-BORDER FLOOD MANAGEMENT IN BENGAWAN SOLO HULU WATERSHED - Sofyan Sholeh; Yasin Yusup (GeoEco, 2023)
Cross-border floods are not only cross-country and cross-province floods but also include cross-district/city floods. The flood that occurred in Sukoharjo Regency was a cross-border flood (cross-border flood) covering four upstream districts, namely Boyolali, Klaten, Wonogiri and Karangnanyar Regencies. The management needed concerning cross-border flooding is the handling of integrated cross-border synergies that enter the Watershed (DAS) with countermeasures, not only structural but non-structural, and involving all stakeholders. This study uses a combination of spatial science and critical human geography paradigms so that the appropriate research design is a mixed method, namely research with both quantitative and qualitative techniques. The critical human geography paradigm is also used here in conjunction with the political ecology approach in tracing the increased risk of flood disasters associated with an expanded urbanization process, an approach derived from production space theory. The results of this study show that the integration of disaster management between regions is very important, both upstream and downstream. Human activities in the upstream region greatly affect the downstream region